Rethinking prosecutorial discretion: towards a moral cartography of prosecutors - Tuesta, Diego (The British journal of criminology, 2021)
This article examines the justifications that a group of prosecutors employs when coordinating human trafficking investigations in the Amazon. The study is based on interviews with officials who work in Madre de Dios, Peru, a region affected by small-scale gold mining, whose demand for labour has increased the incidence of human trafficking. I draw from Boltanski and Thévenot’s polity model to elucidate three moral principles regularly endorsed by prosecutors in the course of criminal investigations: efficiency, civic and domestic values. Together these comprise a moral cartography of prosecution. This study from the Global South contributes to a more holistic—and pragmatic—understanding of prosecutors’ charging decisions, complementing research approaching this topic from the perspective of bounded rationality.